1995
DOI: 10.1074/jbc.270.49.29350
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Analysis of the Fate of Nitric Oxide Synthesized by Macrophages in Vitro

Abstract: To investigate the fate of nitric oxide (NO) synthesized by activated macrophages, the concentrations of NO and its principal reaction products, nitrite (NO2-) and nitrate (NO3-), were measured as a function of time in suspension cultures of RAW264.7 macrophages attached to microcarrier beads. Synthesis of NO became evident 2-5 h after stimulation of the cells, and steady concentrations of NO were achieved after about 9 h. The appearance of NO in the extracellular fluid coincided with the appearance of NO2- an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
116
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(135 citation statements)
references
References 24 publications
18
116
1
Order By: Relevance
“…Decreased inducible NOS induction cannot account for cellular resistance, as both RES and RAW 264.7 macrophages clearly responded to these agonists. Consistent with published observations (33,34), RAW 264.7 macrophages produced approximately equal amounts of both nitrite and nitrate. The increased production, which is not statistically significant, of nitrate in RES cells over RAW 264.7 macrophages might be related to increased ONOO Ϫ formation, as the decomposition of ONOO Ϫ under cellular conditions is rather complex, depending upon the production rate of both O 2 .…”
Section: Discussionsupporting
confidence: 80%
“…Decreased inducible NOS induction cannot account for cellular resistance, as both RES and RAW 264.7 macrophages clearly responded to these agonists. Consistent with published observations (33,34), RAW 264.7 macrophages produced approximately equal amounts of both nitrite and nitrate. The increased production, which is not statistically significant, of nitrate in RES cells over RAW 264.7 macrophages might be related to increased ONOO Ϫ formation, as the decomposition of ONOO Ϫ under cellular conditions is rather complex, depending upon the production rate of both O 2 .…”
Section: Discussionsupporting
confidence: 80%
“…The present study shows that, over a range of concentrations covering those encountered in itro following constitutive or inducible NO synthase activity [22][23][24], NO can be consumed as a result of the presence of two common constituents of cellculture media : riboflavin and Hepes buffer. The combination of the two ingredients under normal laboratory lighting conditions leads to a greatly amplified quench of the NO signal.…”
Section: Discussionmentioning
confidence: 77%
“…Lewis et al (28) observed that activated macrophages release more NO 2 Ϫ than expected and considered Equation 1 as a pos- Table I were replotted as ln((k 1 )/(k 2 )) with 2 Ϫ formation under physiological conditions, we studied the reaction of peroxynitrite with NO using both stopped-flow kinetic spectroscopy and an NO-sensitive electrode. These experiments yielded an apparent second order rate constant of 9.1 ϫ 10 4 M Ϫ1 s Ϫ1 , which is in the same order of magnitude as the rate constant determined for peroxynitrite reacting with CO 2 (42).…”
Section: Discussionmentioning
confidence: 99%
“…However, in contrast with the widely held view that peroxynitrite decomposes exclusively to NO 3 Ϫ , considerable amounts of NO 2 Ϫ were also found as a major stable product of SIN-1 or NO synthase under physiological conditions. 2 Similarly, excess NO 2 Ϫ formation was observed in peroxynitrite producing cells (28), suggesting that additional as yet unidentified reactions contribute to peroxynitrite decomposition.…”
mentioning
confidence: 99%